2020
DOI: 10.3390/en13246698
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Anisotropic Influence of Joint Spacing on Mechanical Behavior of Rock Mass Models under Uniaxial Compression

Abstract: Mechanical properties of rock masses are dominated by the nonlinear response of joints and their arrangement. In this paper, combined influences of joint spacing (s) and joint inclination angle (β) on mechanical behavior of rock mass models with large open joints under uniaxial compression were investigated by PFC modeling. With a large amount of local measurement circles placed along the pre-defined measurement lines (ML), stresses and joint response parameters at different scales (the measurement circles, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This paper proposes a relationship between E and PJS and optimizes its parameters by considering the size change. In existing research, scholars mainly focused on the influence degree (Yang et al, 2019b) (Huang et al, 2019), the influence effect (Chen et al, 2020), and the nonlinear change (Xiong et al, 2019) of the joint parameters. However, they rarely considered the size influence, obtained a relationship for E, or discussed the influence of PJS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper proposes a relationship between E and PJS and optimizes its parameters by considering the size change. In existing research, scholars mainly focused on the influence degree (Yang et al, 2019b) (Huang et al, 2019), the influence effect (Chen et al, 2020), and the nonlinear change (Xiong et al, 2019) of the joint parameters. However, they rarely considered the size influence, obtained a relationship for E, or discussed the influence of PJS.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (2019b) and Huang et al (2019) investigated the influence of joint parameters on E and indicated that joint dip has the greatest effect on E, followed by joint length. Chen et al (2020) discovered that E is affected by the interaction of joints and rock bridges through the study of joint dip and spacing. Cao et al (2018) reported that joint inclination mainly impacts E. Xiong et al (2019) proposed a power function to characterize the nonlinear change of E and joint index.…”
Section: Introductionmentioning
confidence: 99%